Civil Legal Protection for Victims of Default in Digital Financial Services - Fitri Arianti (PT. Anagata Sembagi Education, 2026)
The development of the digital economy in Indonesia has transformed the legal relationship between businesses and consumers, particularly through marketplace platforms that facilitate electronic transactions. This transformation raises legal issues related to the limits of digital platforms' civil liability for consumer losses, particularly given the unclear norms regarding intermediary liability and the basis for claims for breach of contract or unlawful acts. This study aims to analyze the normative foundations of consumer protection in digital transactions and reconstruct the concept of platform civil liability to ensure legal certainty and justice. The research method used is normative legal research with a statutory, conceptual, and analytical approach (analytical and prescriptive approach). Primary and secondary legal materials are analyzed qualitatively using systematic and teleological interpretation techniques to identify unclear norms and formulate normative prescriptions relevant to the dynamics of the digital economy. The results indicate that the Safe Harbor Policy approach is no longer adequate to protect consumers, necessitating the repositioning of platforms as active legal subjects by applying strict liability, vicarious liability, and joint liability models. Reformulating norms through revisions to digital-based consumer protection regulations, integrating personal data protection principles, and strengthening due diligence and transparency obligations in electronic contracts are strategic steps in creating legal certainty that is both adaptive and equitable.